On the possibility to utilize a PCO Edge 4.2 bi scientific CMOS imager for extended ultra violet and soft X-ray photon detection. (1st January 2022) - Menk, R.H.; Arfelli, F.; Cautero, M.; Cautero, G.; Di Fraia, M.; Coreno, M.; Galdenzi, F.; Tutsch, W.
Abstract: A state of the art commercial detector, a PCO Edge 4.2 bi based on a back illuminated sCMOS sensor developed for applications in the visible light/ultra violet regime has been adapted for ultra-high vacuum operations and has been characterized using soft X-ray in the energy range from 30 eV to 1000 eV. The imager features 2048 × 2048 pixel with a pixel size of 6.5 μm × 6.5 μm and allows full frame acquisitions at 48 Hz with a dynamic range of 88 dB at a noise level of 1.9 e − . Spatial resolution and quantum efficiency have been elucidated in the aforementioned energy range at a soft X-ray beam line at Elettra Sincrotrone Trieste. The handiness of the camera as well as its Python library package allows easy and fast integration into the beam line environments of synchrotron sources and free electron lasers.